Toward a Sustainable Campus: Comparison of the Physical Development Planning of Research University Campuses in Malaysia - Nurakmal, Abdullah@ Goh Tuo Ho; Mohd Zulhanif, Abd Razak; Muhammad Farihan Irfan, Mohd Nor; Ismar, M.S. Usman; Adi Irfan, Che-Ani (The Canadian Center of Science and Education, 2011)
Physical development planning is a powerful tool for determining and shaping the living environment of any area, including on campus. If the growing social concern with sustainability is to be addressed by physical planning initiatives, the effectiveness of such initiatives must be assessed soon. The objective of this research is to study the effectiveness of the physical development planning of four research university campuses in Malaysia. These universities have undergone changes to enhance their sustainability. The scope of this research is limited to the physical planning of the campus. Four research universities have been chosen: National University of Malaysia (UKM), University Sains Malaysia(USM), University of Malaya (UM) and University Putra Malaysia (UPM). The research methods used consisted of a questionnaire, behavioral observations and a visual study. A total of 400 respondents were included and were divided equally among the campuses. The resulting data were statistically analyzed. The results from each campus were compared. The results obtained by questionnaire were cross-referenced with the findings obtained from other techniques (behavioral observation and visual study) to obtain a detailed explanation. The research found that many similar problems in physical development planning have arisen on each campus. However, the extent and severity of the problems vary based on the individual approach taken toward physical development planning. The results show that the most compact campus, USM has the fewest problems when compared to the other campuses. This finding supports previous research and indicates that a compact campus tends to create a sustainable pattern of life on campus.